Influence of the production system on the surface properties of influenza A virus particles. Issue 10 (18th July 2017) - Hämmerling, Frank; Pieler, Michael M.; Hennig, René; Serve, Anja; Rapp, Erdmann; Wolff, Michael W.; Reichl, Udo; Hubbuch, Jürgen
Abstract: In this study, influenza A/Puerto Rico/8/34 H1N1 virus particles (VP) produced in adherent and suspension Madin Darby canine kidney cells were investigated with a broad analytical toolbox to obtain more information on the VP's surface properties potentially affecting their aggregation behavior. First, differences in aggregation behavior were revealed by VP size distributions obtained via differential centrifugal sedimentation and confirmed by dynamic light scattering. The VP produced in adherent cells showed increased levels of aggregation in a 20 mM NaCl 10 mM Tris‐HCl pH 7.4 low‐salt buffer. This included the formation of multimers (dimers up to pentamers), whereas VP produced in suspension cells displayed no tendency toward aggregate formation. To investigate the cause of these differences in aggregation behavior, the VP samples were compared based on their zeta potential, their surface hydrophobicity, their lipid composition, and the N ‐glycosylation of their major VP surface protein hemagglutinin. The zeta potential and the hydrophobicity of the VP produced in the adherent cells was significantly decreased compared to the VP produced in the suspension cells. The lipid composition of both VP systems was approximately identical. The hemagglutinin of the VP produced in adherent cells included more of the larger N ‐glycans, whereas the VP produced in suspension cells included more of the smaller N ‐glycans. These results indicate that differences in the glycosylation of viral surface proteins should be monitored to characterize VP hydrophobicity and aggregation behavior, and to avoid aggregate formation and product losses in virus purification processes for vaccines and gene therapy.